Fully Biodegradable Microsupercapacitor for Power Storage in Transient Electronics - Lee, Geumbee; Kang, Seung-Kyun; Won, Sang Min; Gutruf, Philipp; Jeong, Yu Ra; Koo, Jahyun; Lee, Sang-Soo; Rogers, John A.; Ha, Jeong Sook (WILEY-V C H VERLAG GMBH, 2017)
In this work, the authors report materials, fabrication strategies, and applications of biodegradable microsupercapacitors (MSCs) built using water-soluble (i.e., physically transient) metal (W, Fe, and Mo) electrodes, a biopolymer, hydrogel electrolyte (agarose gel), and a biodegradable poly(lactic-co-glycolic acid) substrate, encapsulated with polyanhydride. During repetitive charge/discharge cycles, the electrochemical performance of these unusual MSCs is dramatically enhanced, following from the role of pseudocapacitance that originates from metal-oxide coatings generated by electrochemical corrosion at the interface between the water-soluble metal electrode and the hydrogel electrolyte. Systematic studies reveal the dissolution kinetics/behaviors of each individual component of the MSCs, as well as those of the integrated devices. An encapsulation strategy that involves control over the thickness, chemistry, and molecular weight of the constituent materials provides a versatile means to engineer desired functional lifetimes. Demonstration experiments illustrate potential applications of these biodegradable MSCs as transient sources of power in the operation of light-emitting diodes and as charging capacitors in integrated circuits for wireless power harvesting.
Keywords: ELECTROCHEMICAL ENERGY-STORAGE; IN-VITRO ASSESSMENT; MICRO-SUPERCAPACITORS; GEL ELECTROLYTE; DEGRADATION KINETICS; SILICON ELECTRONICS; OXIDE MATERIALS; CHARGE STORAGE; PURE IRON; SOL-GEL